Incidence of Coronary Events and Case Fatality Rate in Relation to Blood Lymphocyte and Neutrophil Counts - Adamsson Eryd, Samuel; Smith, J. Gustav; Melander, Olle; Hedblad, Bo; Engström, Gunnar (Arteriosclerosis, thrombosis, and vascular biology, 2012)
OBJECTIVE—Elevated levels of blood leukocytes have been associated with acute coronary events (CEs), but data on leukocyte subclasses are limited. This study aimed to explore whether blood lymphocyte and neutrophil counts are associated with incidence of CEs and with fatal outcome in subjects who subsequently experienced a first CE. METHODS AND RESULTS—Neutrophil and lymphocyte counts were measured in 27 419 subjects from the general population without a history of CEs, heart failure, or atrial fibrillation. Incidence of CEs was studied in relation to leukocyte counts during a mean follow-up of 13.6 years. Neutrophil but not lymphocyte counts were significantly associated with incidence of CEs. After adjustments for confounding factors, the hazard ratios (95% confidence interval) were 1.00 (reference), 1.07 (0.94–1.23), 1.09 (0.95–1.25), and 1.39 (1.22–1.59) for subjects with neutrophils in the first, second, third, and fourth (highest) sex-specific quartiles, respectively (P for trend <0.001). Of the 1965 subject who had a CE, 471 subjects died on the first day of the CE, in- or outside hospital. The proportions of subjects who died the first day were 19%, 21%, 25%, and 28%, respectively in the first, second, third, and fourth quartiles (P for trend <0.001). CONCLUSION—Increased neutrophil counts are associated with incidence of CEs and increased case-fatality rate after a CE.